ANALISIS TIME DEPOSIT MONEY DI INDONESIA - Triyono Triyono (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2006)
Time deposit is one of the expected banking product can gather people money significantly. Gathered people money can be used to fulfill attainment of economy growth target. In reality, position of time deposit often fluctuate caused many economic factors.This research aim is to examine economic factors which theoretically influence time deposit. The factors are inflation rate, national income, deposit rate, Rupiah exchange rate to dollar and invesment value. Result of the research indicates variables that influence position of time deposit are inflation and time deposit one year before